The Happiness Atmosphere In Classroom As Medium Of Process Foreign Language Teaching - Mislawi Yadi (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
This study aims to determine the results of the teaching process in the classroom with the approach and design of learning happiness atmosphere in classroom which aims to increase mastery of a foreign language (English). This study used a qualitative descriptive method with data collection stages such as data collection steps including setting research boundaries, collecting information through observation, structured (or semi-structured) interviews, documents, visual materials, documenting the results of information in the field . The object of this research ware semester I students who toke speaking I courses at University of Ibrahimy. The stages and teaching in this class were used multiple methods in the stimulus so that students feel happy and happy in class. The research was used student-focused learning approach (student center). The learning model applied were CTL, Communicative approach, feedback review, discussion and natural learning. In the process of learning foreign language mastery in class, students were allowed used bilingual when having difficulty in vocabulary, students were allowed to directly ask their friends when they have difficulties and other friends were advised to provide feedback on their friends' questions, The final results obtained from the learning process with the application of the happiness atmosphere in the classroom turned out to be very positive results and the students were happy, accustomed to the teaching process and continued to apply learning theory to achieve appropriate success.